2020
DOI: 10.34172/ijhpm.2020.62
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Multi-Pronged Psycho-Social Intervention Among People With Mental Health and Epilepsy Problems - A Pre-Post Prospective Cohort Study Set in North India

Abstract: Background: In low- and middle-income settings, many people with mental health problems cannot or do not access psychiatric services. Few studies of people with epilepsy and mental problems have evaluated the effectiveness of a predominantly psycho-social intervention, delivered by lay community workers. The aim of this study was to assess the effectiveness of a community-based complex mental health intervention within informal urban communities while simultaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Previous research and clinical trials have also shown the value of incorporating a multi-level approach to mental health and substance use treatment, addressing individual-, family-, and community-level interventions. Mathias et al found that incorporating multi-pronged elements to care delivery, including increased access to services, greater education around mental health topics, and robust social support networks, was effective in treating patients with severe mental health problems in India (68). In Tanzania specifically, multi-level approaches to mental health care are gaining support (69) and have been locally implemented in the treatment of other medical issues like HIV (70).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research and clinical trials have also shown the value of incorporating a multi-level approach to mental health and substance use treatment, addressing individual-, family-, and community-level interventions. Mathias et al found that incorporating multi-pronged elements to care delivery, including increased access to services, greater education around mental health topics, and robust social support networks, was effective in treating patients with severe mental health problems in India (68). In Tanzania specifically, multi-level approaches to mental health care are gaining support (69) and have been locally implemented in the treatment of other medical issues like HIV (70).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, for men, the linear relationship between alcohol use and depressive symptoms (68). In Tanzania specifically, multi-level approaches to mental health care are gaining support (69) and have been locally implemented in the treatment of other medical issues like HIV (70).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the researcher-participant interaction through frequent monitoring via social media (Whatsapp) during the intervention period, interviews about psychosocial content and application of a physical intervention (tDCS) may act as a social intervention and can explain in part the clinical improvement observed in both groups. Around the world, many types of social and educational interventions are being developed as effective interventions for the improvement of psychiatric disorders and quality of life ( Elafros et al, 2013 ; Nagy and Moore, 2017 ; He et al, 2019 ; Mathias et al, 2020 ; Pandey et al, 2020 ). These models of care provided by a multidisciplinary team specialized in epilepsy can improve the quality of care provided when compared to exclusive medical care, since they provide greater availability of time for care if they are divided among professionals.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of PPSD experience common mental health problems such as anxiety and depression and do not have access to biomedical care and do not have a formal diagnosis. Further detail of the types of problems experienced and demographics of PPSD within the Burans programme are described elsewhere [ 30 , 32 ]. The CHWs working with Burans are women from the local informal urban community, who have completed high schooling and have shown evidence of engaging in their neighbourhood as change agents.…”
Section: Methodsmentioning
confidence: 99%